Stability analysis of rock slopes using the interface contact model and strength reduction method - Yang, Rui; Li, JiaCheng; Bai, Xue; Zeng, Cheng (Frontiers in Earth Science, 2023)
The stability of rock slopes is generally governed by the presence of discontinuities. Discontinuities are simulated using interface contact elements within the theoretical framework of finite difference method. Through the procedure of shear strength reduction on the sliding surface, the safety factor can be determined when all the nodes of interface contact elements are either in sliding or opening. Compared with existing models, the proposed model can simulate discontinuous deformation in a more realistic manner and thus is more effective in engineering practice. The validity of the proposed model is demonstrated by some typical examples of wedges. For the stability problem of key blocks formed by multi structural planes, conventional key block theory can only take no more than two sliding planes into consideration. However, the proposed method can consider roles of all the structural planes in the stability problem, which provides a new effective way in solving the stability problem of key blocks.